Weak activity of haloalkane dehalogenase LinB with 1,2,3-trichloropropane revealed by X-Ray crystallography and microcalorimetry - Monincová, Marta; Prokop, Zbynek; Vévodová, Jitka; Nagata, Yuji; Damborsky, Jirí (Applied and environmental microbiology, 2007)
1,2,3-Trichloropropane (TCP) is a highly toxic and recalcitrant compound. Haloalkane dehalogenases are bacterial enzymes that catalyze the cleavage of a carbon-halogen bond in a wide range of organic halogenated compounds. Haloalkane dehalogenase LinB from Sphingobium japonicum UT26 has, for a long time, been considered inactive with TCP, since the reaction cannot be easily detected by conventional analytical methods. Here we demonstrate detection of the weak activity (k(cat) = 0.005 s(-1)) of LinB with TCP using X-ray crystallography and microcalorimetry. This observation makes LinB a useful starting material for the development of a new biocatalyst toward TCP by protein engineering. Microcalorimetry is proposed to be a universal method for the detection of weak enzymatic activities. Detection of these activities is becoming increasingly important for engineering novel biocatalysts using the scaffolds of proteins with promiscuous activities.
Keywords: molekulární modely; Crystallography, X-Ray; propan; Models, Molecular; kinetika; krystalografie rentgenová; kalorimetrie; Hydrolases; Calorimetry; Sphingomonadaceae; Kinetics; hydrolasy; Propane